Tingkat Kebugaran Jasmani Taruna SMK Negeri 1 Talawi - Sitorus, Ingrid Margaretha; Simatupang, Nurhayati; Ibrahim, Ibrahim (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2024)
This research was carried out to determine whether students' physical fitness levels have met the standards, so it is necessary to carry out a test to assess their physical fitness levels using the Indonesian Physical Fitness Test (TKJI) method. This research uses quantitative descriptive research to describe the results of the physical fitness test for Talawi State Vocational School 1 Cadet in several categories, namely very good, good, moderate, poor, and very poor. The sample consisted of 30 people. The data collection technique in this research used a series of Indonesian Physical Fitness Tests (men) aged 16-19 years. The results of the physical fitness test for Talawi State Vocational School 1 cadets who took the Indonesian Physical Fitness Test (TKJI) with the results obtained: classification with very good grades totaling three cadets (10%), classification with good grades totaling six cadets (20%), classification with moderate scores there were ten cadets (33.33%), classifications with low scores totaled seven cadets (23.33%), and classifications with shallow scores totaled four cadets (13.33%). In conclusion, the level of physical fitness of Talawi State Vocational School 1 cadets is in moderate condition. Keywords: Physical Fitness, Physical Education, TKJI